Sosialisasi Healing Touch sebagai Terapi Non-Farmakologis untuk Nyeri Pasca Imunisasi pada Anak - Lameky, Vernando Yanry; Akollo, Isak Roberth; Patty, Joanna Cristy; Tuhuleruw, Bredlcy Fransiscus; Tomasila, Boy (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2025)
Immunization is crucial for protecting individuals from vaccine-preventable diseases, but pain during and after vaccination can lead to fear and anxiety in children, causing them to refuse subsequent vaccinations. This study aimed to address the lack of knowledge among parents regarding non-pharmacological pain management techniques, specifically healing touch (HT), through a community empowerment partnership (PKM) program. The PKM was conducted as a socialization event for posyandu cadres at the Waihoka Community Health Center on October 30, 2024. Participants completed a pre-test questionnaire, attended a presentation on HT for post-immunization pain management, engaged in a question-and-answer session, and completed a post-test questionnaire. The results showed that before the socialization, most cadres had poor knowledge of non-pharmacological therapies and HT. However, after the event, their knowledge significantly improved, with the majority demonstrating very good understanding. The study concludes that the socialization effectively enhanced the posyandu cadres' knowledge of HT as a non-pharmacological therapy for post-immunization pain management. The authors recommend that the Ambon City Health Office, through the Community Health Center, conduct similar socialization events for parents through posyandu cadres to promote the use of HT in reducing post-immunization pain and anxiety in children.